Teaching for the Future in Early Childhood Education - Licardo, Marta; Mezak, Jasminka; Gencel , İlke Evin (2023)
The monograph focuses on the teaching and learning of children in early childhood education. The international monograph includes contributions by authors from three countries, highlighting different perspectives on contemporary teaching and learning specific to ECE. The monograph is based on the collaboration of researchers from different universities in the Erasmus+ Algolittle project, who have explored important contemporary concepts of teaching in ECE, such as how to develop algorithmic thinking in preschool children, how to teach algorithmic thinking to ECE students, and the relevance of such cognitive skills for future knowledge. The monograph goes beyond the scope of the project by incorporating new scientific findings related to the implementation of various concepts in learning and teaching preschool children, such as executive functions, algorithmic thinking, creativity, problem-based thinking, integration of teaching from different domains, distance learning, specific pedagogical practices, thus presenting a wide range of topics relevant for the development of learning and teaching in early childhood education now and in the future.
Keywords: early childhood education; teaching; learning; algorithmic thinking; cognition